Optimalisasi Pengelolaan Fasilitas Kampus Menggunakan IoT untuk Monitoring Ketersediaan Ruang dan Peralatan - Agung Hidayat; Tata Sutabri (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2025)
The application of Internet of Things (IoT) technology in campus facility management can enhance operational efficiency and effectiveness by monitoring the availability of rooms and equipment in real-time. This study aims to explore the basic concepts and implementation of IoT in managing campus facilities through document analysis. The results show that IoT can assist in managing classrooms and equipment, allowing campus managers to optimize facility usage, reduce wastage, and improve service quality. IoT implementation also facilitates the maintenance and replacement of faulty equipment by utilizing data generated from sensors. However, the main challenges in IoT implementation are related to technological infrastructure and data security, which require special attention to ensure the system operates effectively and securely. Overall, this study concludes that IoT technology provides a solution to improve campus facility management efficiency and supports the creation of a more modern and responsive educational environment.